Layered change log model: bridging between ontology change representation and pattern mining. (7th July 2014) - Javed, Muhammad; Abgaz, Yalemisew M.; Pahl, Claus
To date, no ontology change management system exists that records the ontology changes based on the different levels of granularity. Once changes are performed using elementary–level change operations, they are recorded in the database at the elementary level accordingly. Such a change representation procedure is not sufficient to represent the intuition behind any applied change and thus, cannot capture the semantic impact of a change. In this paper, we discuss the recording of the applied ontology changes in the form of a layered change log. This knowledge–based layered change log facilitates the detection of the similarities within different time series, mining of change patterns and reuse of the knowledge. Here, the lower–level change log is utilised for recording of the applied ontology changes (operational) and mining of the change patterns (analytical). The higher–level change log supports a comprehensive understanding of the ontology evolution.